Bioinspired total synthesis of tetrahydrofuran lignans by tandem nucleophilic addition/redox isomerization/oxidative coupling and cycloetherification reactions as key steps - Jagtap, Pratap R; Císařová, Ivana; Jahn, Ullrich (Organic & biomolecular chemistry, 2018)
A very short three-step approach to trans,trans,trans-2,5-diaryl-3,4-dimethyltetrahydrofuran lignans is reported. The carbon skeleton is assembled in a single step based on an unprecedented tandem reaction consisting of 1,2-addition of aryllithium reagents to α,β-unsaturated aldehydes, ruthenium-catalyzed redox isomerization of the resulting alkoxides to enolates and their dimerization triggered by single electron oxidation. The resulting 2,3-dialkyl-1,4-diketones form with moderate to good d/l-diastereoselectivity and are transformed to the target tetrahydrofuran lignans by reduction and diastereoselective cycloetherification.
Keywords: furany; techniky syntetické chemie; Models, Molecular; Catalysis; Oxidative Coupling; Furans; oxidace-redukce; krystalografie rentgenová; Cyclization; Crystallography, X-Ray; oxidační párování; molekulární modely; Isomerism; lignany; ruthenium; Biomimetics; biomimetika; Chemistry Techniques, Synthetic; Oxidation-Reduction; aldehydy; cyklizace; isomerie; Aldehydes; Ruthenium; Lignans; katalýza